Synthesis and antioxidant activity of long chain alkyl hydroxycinnamates - Menezes, Jose C.J.M.D.S (2019)
Long chain alkyl hydroxycinnamates (8e21) were synthesized from the corresponding half esters of malonic acid (5e7) and benzaldehyde derivatives by Knoevenagel condensation. The total antioxidant capacity of these hydroxycinnamyl esters was evaluated using DPPH and ABTS assays. The observed antioxidant activity was highest for esters of caffeic acid followed by sinapic esters and ferulic esters. The parameters for drug-likeness of these hydroxycinnamyl esters were also evaluated according to the Lipinski’s ‘rule-of-five’. All the ester derivatives were found to violate one of the Lipinski’s parameters (cLogP >5), even though they have been found to be soluble in protic solvents. The predictive topological polar surface area (TPSA) data allow concluding that they could have a good capacity for penetrating cell membranes. Therefore, one can propose these novel lipophilic compounds as potential antioxidants for tackling oxidative processes.